Sub‐Micrometer Structure Formation during Spin Coating Revealed by Time‐Resolved In Situ Laser and X‐Ray Scattering. (12th September 2017) - van Franeker, Jacobus J.; Hermida‐Merino, Daniel; Gommes, Cedric; Arapov, Kirill; Michels, Jasper J.; Janssen, René A. J.; Portale, Giuseppe
Abstract: Solution‐processed thin polymer films have many applications, such as organic electronics and block‐copolymer nanofabrication. These films are often made by spin coating a solution that contains one or more solids and can show different phase‐separated structures. The formation mechanism of the droplet‐like morphology is studied here by processing polystyrene (PS) and a fullerene derivative ([6, 6]‐phenyl‐C71 ‐butyric acid methyl ester, [70]PCBM) from o ‐xylene. The final structure consists of [70]PCBM droplets partially embedded in a PS‐rich matrix showing interdomain distance of 100–1000 nm as determined from transmission electron microscopy and grazing incidence small angle X‐ray scattering (GISAXS). To elucidate the formation of these morphologies in real time, ultrafast in situ GISAXS coupled with laser interferometry and laser scattering is performed during spin coating. In situ thickness measurements and laser scattering show that liquid–liquid phase separation occurs at ≈70 vol% solvent. Subsequently, in only 100–400 ms, almost dry [70]PCBM domains start to protrude from the swollen PS‐rich matrix. These results are used to verify the ternary phase diagram calculated using Flory–Huggins theory. The discussed multitechnique approach can be applied to study fundamental aspects in soft matter such as phase separation in thin films occurring at very short time scales. Abstract : Phase separation in droplet‐forming polymer:fullerene mixtures is studied in real time by performing simultaneously in situ X‐ray scattering, laser scattering, and thickness measurements. In situ observations combined with ex situ results and data modeling show how droplet formation involves stages like liquid–liquid phase separation and solvent partitioning, resulting in thin films featuring both embedded phase separation and surface topography.